2021
DOI: 10.1155/2021/2005369
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Length Predicts the Incidence of Microembolic Signals in Acute Anterior Circulation Stroke

Abstract: Microembolic signals (MES) of the carotid artery are associated with plaque destabilization and reoccurrence of stroke. Previous studies have focused primarily on the degree of carotid artery stenosis and plaque components, and the relationship between plaque length and microembolic sign has received little attention. We aimed to find the association between carotid plaque length (CPL) and the presence of MES. We conducted a retrospective observational cross-sectional study. A total of 84 acute anterior-circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…In addition, we also found that plaque surface irregularity, length, and area, but not plaque thickness were associated with the presence of cerebral symptoms. Several studies have demonstrated a significant correlation between the presence of atherosclerotic plaques with an irregular surface and cerebral symptoms [ 23 , 44 , 45 ], with a reported association between carotid plaque length and area and the presence of micro-emboli and increased risk of ischemic stroke or transient ischemic attack in patients with low-grade carotid stenosis [ 25 , 46 ]. It has been reported that the growth of a carotid plaque’s length is more rapid than its corresponding thicknesses [ 46 , 47 ], suggesting that plaque area is more influenced by the length of the plaque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also found that plaque surface irregularity, length, and area, but not plaque thickness were associated with the presence of cerebral symptoms. Several studies have demonstrated a significant correlation between the presence of atherosclerotic plaques with an irregular surface and cerebral symptoms [ 23 , 44 , 45 ], with a reported association between carotid plaque length and area and the presence of micro-emboli and increased risk of ischemic stroke or transient ischemic attack in patients with low-grade carotid stenosis [ 25 , 46 ]. It has been reported that the growth of a carotid plaque’s length is more rapid than its corresponding thicknesses [ 46 , 47 ], suggesting that plaque area is more influenced by the length of the plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a significant correlation between the presence of atherosclerotic plaques with an irregular surface and cerebral symptoms [23,44,45], with a reported association between carotid plaque length and area and the presence of micro-emboli and increased risk of ischemic stroke or transient ischemic attack in patients with low-grade carotid stenosis [25,46]. It has been reported that the growth of a carotid plaque's length is more rapid than its corresponding thicknesses [46,47], suggesting that plaque area is more influenced by the length of the plaque. Furthermore, our analysis revealed no significant difference in cIMT between symptomatic and asymptomatic patients.…”
Section: Plos Onementioning
confidence: 99%
“…For intracranial atherosclerosis stenting, a longer stenosis length has been reported to be an independent risk factor for ISR [ 26 ]. Subsequently, carotid plaque length was studied as an independent predictor of carotid plaque leading to microembolic signals [ 9 ] and ipsilateral carotid blood flow compromise [ 27 ] and was found to be independently associated with perioperative stroke and death in patients treated with CEA and CAS [ 28 ]. In addition, carotid soft plaque thickness is associated with plaque vulnerability, with each 1-mm increase in plaque thickness associated with a 2.7-fold increase in the odds of having a stroke or TIA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plaque characteristics assessed by carotid computed tomography angiography (CTA), such as plaque length [ 9 ], plaque texture [ 10 ], plaque thickness [ 11 ], plaque ulceration [ 12 ], and plaque enhancement [ 13 ], are strongly associated with the development of ischemic stroke. Accurate identification of these features can help in risk stratification among patients with carotid atherosclerotic stenosis.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Similar findings were obtained in another study in patients with symptomatic carotid artery atherosclerosis whose carotid plaque length was independently associated with microembolic signals. 37 This mechanism may help explain why increasing plaque length is related to AAE.…”
Section: Discussionmentioning
confidence: 99%